School Violence in South Korea from the Perspective of Coaching Psychology and Counseling - Seok, Jong-Ok; Chung, Jun-Ki (International Journal of Membrane Science and Technology, 2023)
One of the most pressing problems facing South Korean society today is school violence. This problem causes many instructors to feel hopeless, and many of them take their own lives as a result. This study intends to shed light on the causes of such violence as well as its solutions via the lenses of coaching psychology and counseling. In this study, we will show that school violence in Korea is a result of a cultural phenomenon that is connected with a number of societal issues as Korea transitions into a post-modern society, rather than just being a result of conflicts between students and teachers or parents and teachers.